Synthesis and characterization of ZnO nanoparticles - Ooi, Sheue Lin (Universiti Malaysia Sarawak (UNIMAS), 2012)
ZnO nanoparticles have drawn a widespread attention recently due to their novel properties which contribute to various applications especially in optoelectronic devices. In this research project, the spherical ZnO nanoparticles with average size of less than 50 nm were successfully synthesized and their optical properties were measured. In order to maximize its efficiency, surface modification with surfactants is vital as ZnO nanoparticles easily agglomerate. In this study, precipitation method was applied where surfactants such as succinic acid, carboxymethyl cellulose, and adipic acid were used for enhanced properties. The addition of surfactants controlled the particle size and reduced the formation of agglomerates and at the same time helped to produce more homogenous and uniformly dispersed particles.